F47. Screening of GLE1 mutations in Chinese amyotrophic lateral sclerosis patients. (May 2018) - Zhang, Kang; Liu, Qing; Shen, Dongchao; Tai, Hongfei; Fu, Hanhui; Ding, Qingyun; Liu, Shuangwu; Wang, Zhili; Li, Xiaoguang; Liu, Mingsheng; Zhang, Xue; Cui, Liying; et al.
Abstract : Introduction: Amyotrophic lateral sclerosis (ALS) is a fatal disease involving both upper and lower motor neuron, resulting in a 3–5 year of survival from symptom onset caused by rapidly progressive paralysis and respiratory failure. It is etiologically heterogeneous. Approximately 90% of ALS cases are sporadic (SALS) with unknown causes. But The remaining 10% of patients have a family history (FALS) and harbor a causative gene mutation, reflecting genetic factor play an important role in the pathogenesis of ALS. To date, mutations in over 20 genes have been reported in ALS populations. Mutations in GLE1 are the causation of two fetal motoneuron diseases: lethal congenital contracture syndrome 1 (LCCS1) and lethal arthrogryposis with anterior horn cell disease (LAAHD). Recently, Kaneb et al. identified GLE1 variants within sporadic and familial Caucasian ALS cases, supporting defects in RNA metabolism were associated with pathogenesis of ALS. However, GLE1 mutations have not been investigated in Chinese ALS patients so far. Accordingly, we evaluated whether GLE1 mutations harbored in ALS patients from mainland China. Methods: The current study recruited probands of 20 ALS families (mean age of onset was 50.1 ± 10.9 years; 10 females, 10 males), 230 SALS patients (mean age of onset was 52.1 ± 11.9 years; 96 females, 134 males). All 16 exons (plus 50 bp of flanking introns) of GLE1 (NM_001003722.1) including the entire coding region were amplified using polymerase chain reaction (PCR). The reaction conditions of PCR were as follows: 5 min of denaturation at 95 °C, 8 cycles were used with 20 s at 94 °C, 20 s at 65 °C (decreasing by 1 °C with each cycle) and 30 s at 72 °C. 20 s at 94 °C, 20 s at 58 °C and 30 s at 72 °C for the subsequent 34 cycles, a final extension step at 72 °C for 5 min. PCR products were subjected to Sanger sequencing using ABI 3730 automated DNA-sequencing system (Applied Biosystems). The sequences were aligned with reference sequence using CodonCode Aligner. Results: GLE1 mutation screening of 250 ALS cases revealed 4 synonymous genetic variants(c.444G > A, p. R148R; c.946C > A, p. R316R; c.1641T > C, p. Y547Y; c.2082C > T, P. S694S), which presented in dbSNP database. Bioinformatic analysis using ESE finder and Human Splicing Finder 3.0 showed that all the silent mutations did not affect transcription process. We did not identify any novel or reported rare variants in all 16 coding exons of GLE1 from 250 Chinese ALS patients. Conclusion: In summary, our results suggested that GLE1 mutations are not common in FALS and SALS of Chinese origin. Further study in larger and additional populations would be required to evaluate the role of GLE1 in ALS causation.